2016
DOI: 10.1136/sextrans-2016-052738
|View full text |Cite|
|
Sign up to set email alerts
|

Identifying factors that lead to the persistence of importedgonorrhoeaestrains: a modelling study

Abstract: The imported NG strain is unlikely to persist as a result of a single importation event. However, the probability of persistence increases if the imported NG strain is resistant to treatment, can form mixed infections with the local NG strain or there are frequent importation events. Identification of the factors that determine the likelihood of persistence of an imported NG strain could contribute to our capacity to respond appropriately and in a timely fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
(12 reference statements)
2
6
0
Order By: Relevance
“…Estimates for partnership durations and homophily rates were similar in all three scenarios, indicating quite robust results. The estimates for the duration of steady partnerships were comparable to the data reported by the ACS study [ 56 ] (1355 days), as well as studies from Hui et al [ 22 , 23 , 24 ] and Kasaie et al [ 26 ], all reporting an average duration of 4 years. The average duration for persistent casual partnerships was affected by the activity group of the two partners, with a much shorter duration if one of the two partners was a HA-MSM.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Estimates for partnership durations and homophily rates were similar in all three scenarios, indicating quite robust results. The estimates for the duration of steady partnerships were comparable to the data reported by the ACS study [ 56 ] (1355 days), as well as studies from Hui et al [ 22 , 23 , 24 ] and Kasaie et al [ 26 ], all reporting an average duration of 4 years. The average duration for persistent casual partnerships was affected by the activity group of the two partners, with a much shorter duration if one of the two partners was a HA-MSM.…”
Section: Discussionsupporting
confidence: 85%
“…Several modeling studies have described the transmission of CT and NG among MSM [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], which cluster in a few Western countries, mainly from the US [ 9 , 13 , 14 , 19 , 25 , 26 , 27 , 28 , 35 , 36 ] and Australia [ 18 , 22 , 23 , 24 , 32 , 40 , 41 , 42 , 43 ]. In Europe, notable modeling studies have been conducted in the UK [ 31 , …”
Section: Introductionmentioning
confidence: 99%
“…MSM have more bacterial STI diagnoses and greater exposure to antimicrobial drugs, thereby increasing selection pressures for AMR, a hypothesis supported by mathematical models (21)(22)(23)(24). Resistant strains also might persist in the absence of selective pressure because the organism's biologic fitness is unaffected or compensatory mutations mitigate a deleterious effect (25)(26)(27). By combining WGS, epidemiologic, and phenotypic data, we found that reduced susceptibility to ceftriaxone and cefixime emerged repeatedly in separate sexual networks in England.…”
Section: Discussionmentioning
confidence: 72%
“…Isolates from persons who recently had a travel-associated sexual partnership were more likely to be infected with N. gonorrhoeae that was resistant to ciprofloxacin. Although de novo development of high-level resistance to azithromycin in the United Kingdom has been described, some studies have concluded that importation events probably initiate AMR spread in countries with low population prevalence, such as England (11,27,28). The success of antimicrobial stewardship policies and compliance with treatment guidelines that aim to curtail AMR in the endemic gonococcal population in England could be undermined by the importation and subsequent spread of resistant isolates.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we develop an anatomic site-specific individual-based model of gonorrhoea transmission in an urban Australian MSM population. Although similar in some aspects to other site-specific models of NG in MSM (e.g., two Australian studies [18,20] and two US studies [21,22]), this model has been specifically developed to examine outbreak control strategies for imported NG infection. Here, we evaluate the potential impact of community and individual-level test-and-treat strategies to control outbreaks of imported NG strains in the Australian MSM population.…”
Section: Competing Interestsmentioning
confidence: 99%